2020
DOI: 10.1007/s40891-020-00235-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Group of the Inorganic Additives on Index and Microstructural Properties of Expansive Soil

Abstract: Expansive soils exhibit volume-change behaviour on exposure to moisture changes due to the presence of the montmorillonite mineral. The swell-shrink behaviour of these soils could lead to instability of the structures found on them, specifically the lightweight structures and pavements. Chemical stabilisation of expansive soils has always proven to be more successful in mitigation of swelling, compared to other methods of removal, replacement, and structural alterations. The present study focuses on the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Treating expansive soils has also received attention in the scholarly literature. Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Treating expansive soils has also received attention in the scholarly literature. Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Treating expansive soils has also received attention in the scholarly literature. Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested.…”
Section: Introductionmentioning
confidence: 99%